Paramagnetic iron-containing ionic liquid crystals - Wang, Xinjiao; Valldor, Martin; Spielberg, Eike T.; Heinemann, Frank Wilhelm; Meyer, Karsten; Mudring, Anja Verena (Journal of Molecular Liquids, 2020)
Iron-containing ionic liquid crystals of N,N′-dialkylimidazolium salts ([(CnH2n+1)2IM]3[Fe(CN)6], with n = 12 (1), 14 (2), 16 (3), 18 (4), IM = imidazolium) were prepared and their structures and properties were characterized. Differential scanning calorimetry (DSC), polarizing optical microscopy (POM) as well as powder X-ray diffraction (PXRD) analysis reveal for all compounds thermotropic liquid crystalline behavior. The observed textures point to smectic A and smectic X phases. The crystal structure of the solvate [C12C12IM]3[Fe(CN)6]·2 DMSO (DMSO = dimethylsulfoxide) was examined by single crystal X-ray diffraction analysis which reveals two crystallographically independent [C12C12IM]+ cations with different conformation, U-shape and rod-shape, together with a nearly ideal octahedral [Fe(CN)6]3− anion and two DMSO solvent molecules. The crystal packing is characterized by alternating bilayers of almost linearly arranged imidazolium cations with the U-shaped cations being arranged in a head-to-head fashion and the cations' hydrophobic dodecyl chains being interdigitated. Magnetic measurements for compounds 1–4 show paramagnetic moments, μeff, of 1.7 μB, which are close to the theoretically expected value for a d5 low-spin Fe3+ spin-only S = 1/2 system (μeff s.o. = 1.73 μB). It was possible to obtain an Fe3+ containing ILC material that combines liquid crystalline behavior over a large mesophase window (from 33 °C to 170 °C) with high magnetic susceptibility by mixing compound 3 with [C16C16IM][FeCl4] (5), which contains the d5 high-spin Fe3+ ion (S = 5/2). All compounds are highly hydrophobic and stable in the atmosphere indicating a great potential of applications as functional materials.
CRIS-Team Scopus Importer:2020-03-17